Enhancing antitumor activity of herceptin in HER2-positive breast cancer cells: a novel DNMT-1 inhibitor approach - Li-li Ren; Yan-ru Song; Zhen-chuan Song; Hua Yang; Qian Zhang; Meng-meng Ji; Na Xiao; Ming Wen; Ji-hai Wang (Discover Oncology, 2024)
Abstract HER2 antagonists remain the cornerstone of therapy for patients with HER2-positive breast cancer. This study introduces a novel small-molecule inhibitor of DNA methyltransferase 1 (DNMT-1), referred to as DI-1, designed to synergize with HER2 antagonists in treating HER2-positive breast cancer cells. Clinical data reveal a negative correlation between DNMT-1 expression and PTEN levels, and a positive correlation with the methylation rates of PTEN's promoter. In experiments with SKBR3 and BT474 cells, DI-1 effectively reduced the methylation of PTEN's promoter region, thereby upregulating PTEN expression. This upregulation, in turn, enhanced the cells' sensitivity to HER2 antagonists, indicating that DI-1’s mechanism involves inhibiting DNMT-1’s recruitment to PTEN's promoter region. Consequently, by increasing PTEN expression, DI-1 amplifies the sensitivity of HER2-positive breast cancer cells to treatment, suggesting its potential as a promising therapeutic strategy in this context.